1975
DOI: 10.3168/jds.s0022-0302(75)84791-6
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of Arginine and Ornithine in the Cow and Rabbit Mammary Tissue

Abstract: Amino acid uptake by the bovine mammary gland was determined by arteriovenous difference. Extraction of arginine from the plasma by the lactating bovine mammary gland was in excess of requirements for milk protein synthesis. Ornithine and citrulline also were extracted by the gland but are not in milk protein. Incubations of slices of lactating mammary tissue from cows and rabbits indicate that nonessential amino acids, especially proline and glutamate, are the major end products of arginine and ornithine meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
16
0

Year Published

1980
1980
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 16 publications
1
16
0
Order By: Relevance
“…The output of proline in the milk of goats [255], sheep [256], cows [257] and pigs [258] greatly exceeds the uptake of proline by the lactating mammary gland, whereas the uptake of plasma arginine by lactating mammary glands greatly exceeds the output of arginine in the milk [255][256][257][258][259]. Studies with lactating mammary tissues have demonstrated arginine-dependent production of proline [249,257], but there was little or no synthesis of proline from glutamate [249] because of the absence of P5C synthetase [47,249]. Uptake of ornithine and citrulline (potential precursors for proline synthesis) by the lactating mammary gland is relatively low compared with that of arginine [256,257].…”
Section: Arginase and Proline Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…The output of proline in the milk of goats [255], sheep [256], cows [257] and pigs [258] greatly exceeds the uptake of proline by the lactating mammary gland, whereas the uptake of plasma arginine by lactating mammary glands greatly exceeds the output of arginine in the milk [255][256][257][258][259]. Studies with lactating mammary tissues have demonstrated arginine-dependent production of proline [249,257], but there was little or no synthesis of proline from glutamate [249] because of the absence of P5C synthetase [47,249]. Uptake of ornithine and citrulline (potential precursors for proline synthesis) by the lactating mammary gland is relatively low compared with that of arginine [256,257].…”
Section: Arginase and Proline Synthesismentioning
confidence: 99%
“…Studies with lactating mammary tissues have demonstrated arginine-dependent production of proline [249,257], but there was little or no synthesis of proline from glutamate [249] because of the absence of P5C synthetase [47,249]. Uptake of ornithine and citrulline (potential precursors for proline synthesis) by the lactating mammary gland is relatively low compared with that of arginine [256,257]. There is virtually no proline catabolism by the mammary gland because it lacks proline oxidase [249].…”
Section: Arginase and Proline Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Cow mammary tissue was cultured in media with increasing concentrations of proline. (Clark et al 1975;Verbeke et al 1968). This process is connected with a substantial loss of nitrogen.…”
mentioning
confidence: 99%
“…tein commonly supplied to the duodenum (up to 5Va) by the usual diets, -207o of the proline needed for casein synthesis is synthesized from arginine and ornithine (Clark et al 1975;Verbeke et al 1968). This process is connected with a substantial loss of nitrogen.…”
mentioning
confidence: 99%